In Situ Grown Single‐Atom Cobalt on Polymeric Carbon Nitride with Bidentate Ligand for Efficient Photocatalytic Degradation of Refractory Antibiotics. Issue 29 (22nd June 2020) - Yang, Yang; Zeng, Guangming; Huang, Danlian; Zhang, Chen; He, Donghui; Zhou, Chengyun; Wang, Wenjun; Xiong, Weiping; Song, Biao; Yi, Huan; Ye, Shujing; Ren, Xiaoya
Abstract: Semiconductor photocatalysis is a promising technology to tackle refractory antibiotics contamination in water. Herein, a facile in situ growth strategy is developed to implant single‐atom cobalt in polymeric carbon nitride (pCN) via the bidentate ligand for efficient photocatalytic degradation of oxytetracycline (OTC). The atomic characterizations indicate that single‐atom cobalt is successfully anchored on pCN by covalently forming the CoO bond and CoN bond, which will strengthen the interaction between single‐atom cobalt and pCN. This single‐atom cobalt can efficiently expand optical absorption, increase electron density, facilitate charge separation and transfer, and promote OTC degradation. As the optimal sample, Co(1.28%)pCN presents an outstanding apparent rate constant for OTC degradation (0.038 min −1 ) under visible light irradiation, which is about 3.7 times than that of the pristine pCN. The electron spin resonance (ESR) tests and reactive species trapping experiments demonstrate that the 1 O2, h +, O2 −, and OH are responsible for OTC degradation. This work develops a new way to construct single‐atom‐modified pCN and provides a green and highly efficient strategy for refractory antibiotics removal. Abstract : Single‐atom cobalt is in situ grown on polymeric carbon nitride by the CoO and CoN bidentate ligands, exhibiting superb photocatalytic performance in the degradation of oxytetracycline under visible light irradiation (λ > 420 nm) due to the improved molecular oxygen activation ability induced by the boosted exciton dissociation and accelerated charge transfer.